Answer :

For the given equation kx2 + 2x + 3k = 0


a = k b = 2 c = 3k comparing with ax2 + bx + c = 0


Sum of the roots


Product of the roots


Sum of roots is equal to their product:


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses